University partnerships for pre-service and teacher development - Cozza, Barbara; Blessinger, Patrick (Bingley, U.K. : Emerald Publishing Limited, 2017)
This volume examines the diverse ways in which universities and colleges around the world are partnering and collaborating with other institutions to fulfill their missions and visions. University partnerships not only include collaborations between universities but also include university-school (basic education) collaborative partnerships to improve local school systems. The increasing pressures to remove access and participation barriers, and to mitigate practices that restrict the free flow of education across borders, have created a growing global space for educational services of all types. As a result, traditional institutional boundaries have expanded to better respond to the increasing pressures placed on them by the growing demand for higher education services. This edited volume will specifically explore university partnerships for preservice and teacher development.
Prelims -- Concepts and principles -- Successful practices -- About the authors -- Author index -- Subject index.
Includes bibliographical references and index.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Teachers -- Training of